2019
DOI: 10.3389/fmars.2019.00361
|View full text |Cite
|
Sign up to set email alerts
|

Waves and Swells in High Wind and Extreme Fetches, Measurements in the Southern Ocean

Abstract: The generation and evolution of ocean waves by wind is one of the most complex phenomena in geophysics, and is of great practical significance. Predictive capabilities of respective wave models, however, are impaired by lack of field in situ observations, particularly in extreme Metocean conditions. The paper outlines and highlights important gaps in understanding the Metocean processes and suggests a major observational program in the Southern Ocean. This large, but poorly investigated part of the World Ocean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 66 publications
0
32
0
1
Order By: Relevance
“…The trends in P w show a latitudinal variation, with the highest values found in the Southern Ocean, with an increase from 0.2 to 0.4 kW/m/year, and the lowest values found in the tropical belts, from 0.02 to 0.15 kW/m/year. These effects had been already demonstrated in global winds (Ribal & Young, 2019), and in wave climate (Babanin et al., 2019; Ribal & Young, 2019; Young et al., 2011). The trends 1985–2018 resemble the robust consensus that an increment of the mean and high percentiles of H s in the Southern Ocean exists (Ribal & Young, 2019; Young et al., 2011).…”
Section: Global Trendsmentioning
confidence: 69%
See 1 more Smart Citation
“…The trends in P w show a latitudinal variation, with the highest values found in the Southern Ocean, with an increase from 0.2 to 0.4 kW/m/year, and the lowest values found in the tropical belts, from 0.02 to 0.15 kW/m/year. These effects had been already demonstrated in global winds (Ribal & Young, 2019), and in wave climate (Babanin et al., 2019; Ribal & Young, 2019; Young et al., 2011). The trends 1985–2018 resemble the robust consensus that an increment of the mean and high percentiles of H s in the Southern Ocean exists (Ribal & Young, 2019; Young et al., 2011).…”
Section: Global Trendsmentioning
confidence: 69%
“…However, both of them weaken the Walker Circulation (Lu et al, 2009;Lucas et al, 2014;Reichler, 2009). From this, some responses in global warming and in ENSO warm phases are similar, particularly the increase in wave power in the Southern Ocean, where the swells are irradiated toward the ocean basins (Babanin et al, 2019) following the patterns identified by Alves (2006). In the areas affected by these swells, such as Australia, Africa, or America, the phenomena, when coupled, can expose these coasts to high levels of risk.…”
Section: Enso Coastal Hazards and Climate Changementioning
confidence: 87%
“…It can be also noticed from Figure 1 that in the South Pacific and Atlantic Oceans and in the southern part of the Indian Ocean over extended areas, the highest values of the mean wave power (higher than 80 kW/m) can be found. This is due to the influence of the Southern Ocean (an extended water body without any land that encircles Antarctica) with extended fetches for wave developments and an upward trend of the H S associated with the global warming [56,57]. The most energetic coastal regions are in the southwestern parts of South America, South Africa, and also in the southern coast of Australia.…”
Section: Global Wave Power According To Era5 Databasementioning
confidence: 99%
“…This is exacerbated in the Southern Ocean (Zieger et al., 2015)—a region covering an uninterrupted band of water around Antarctica south of the main landmasses of Africa, Australia, and South America—that is dominated by strong westerly winds, which blows all‐the‐year‐round with almost unlimited fetches and speed in excess of 13 m/s during summer months and 18 m/s during winter months (Young et al., 2020). These intense winds generate some of the fiercest waves on the planet with high percentiles of wave height exceeding 5 m during summer and 7 m during winter (e.g., Babanin et al., 2019; Barbariol et al., 2019; Letraon et al., 2019; Vichi et al., 2019; Young et al., 2020).…”
Section: Introductionmentioning
confidence: 99%